Humanized Mouse Models of Systemic Lupus Erythematosus: Opportunities and Challenges - Chen, Jiaxuan; Liao, Shuzhen; Zhou, Huimin; Yang, Lawei; Guo, Fengbiao; Chen, Shuxian; Li, Aifen; Pan, Quanren; Yang, Chen; Liu, Hua-feng; Pan, Qingjun (Frontiers in Immunology, 2022)
Animal models have played a crucial role in the understanding of the mechanisms and treatments of human diseases; however, owing to the large differences in genetic background and disease-specific characteristics, animal models cannot fully simulate the occurrence and progression of human diseases. Recently, humanized immune system mice, based on immunodeficient mice, have been developed that allow for the partial reconstruction of the human immune system and mimic the human in vivo microenvironment. Systemic lupus erythematosus (SLE) is a complex disease characterized by the loss of tolerance to autoantigens, overproduction of autoantibodies, and inflammation in multiple organ systems. The detailed immunological events that trigger the onset of clinical manifestations in patients with SLE are still not well known. Two methods have been adopted for the development of humanized SLE mice. They include transferring peripheral blood mononuclear cells from patients with SLE to immunodeficient mice or transferring human hematopoietic stem cells to immunodeficient mice followed by intraperitoneal injection with pristane to induce lupus. However, there are still several challenges to be overcome, such as how to improve the efficiency of reconstruction of the human B cell immune response, how to extend the lifespan and improve the survival rate of mice to extend the observation period, and how to improve the development of standardized commercialized models and use them. In summary, there are opportunities and challenges for the development of humanized mouse models of SLE, which will provide novel strategies for understanding the mechanisms and treatments of SLE.